Socio-demographic factors affecting fertility in Poblacion, Carles, Iloilo. - Quintilla, Mae L
In spite of the massive campaigns to practice family planning, the problem of overpopulation still confronts our society. this study on the relationship of socio-demographic factors to fertility seeks to determine if, indeed these affect fertility.Specifically this study aims to: 1) find out if there is a relationship between husbands' educational attainment and fertility, 2) find out if there is a relationship between wives' educational attainment to fertility, 3) find out if there's a relationship between husbands' employment status and fertility, 4) find out if there's a relationship between wives status employment and fertility, 5) find out if there's a relationship between husbands' age at marriage and fertility, 6) find out if there's a relationship between wives' age at marriage and fertility., The study was conducted in Brgy.. Poblacion, Carles, from Nov. 4 to Nov. 9, 1996. Data were gathered through interview schedule. Respondents of the study were 35 male parents and 35 female parents. The study made use of chi-square and Pearson r in the analysis of data. Results of the study showed that there is a negative relationship among four variables in relation to fertility. These are husbands' educational attainment, husbands' age at marriage, wives' educational attainment and wives' age at marriage. The wives' employment status also showed a significant relationship to fertility, while husbands' employment status showed no significant relationship to fertility. This shows that socio-demographic factors affect fertility.